FDA-approved kinase inhibitors: a promising therapeutic avenue for traumatic brain injury - Dezhu Gao; Yu Shi; Zhiliang Wang; Weiming Liu (Exploration of Drug Science)
Traumatic brain injury (TBI) is a complex disease that leads to significant mortality and disability worldwide each year. TBI disrupts the normal activity of kinases and molecular signaling pathways, but the effective therapeutic methods for patients remain limited. Nowadays, kinase inhibitors approved by the Food and Drug Administration (FDA) mainly for cancer treatment have shown potential effects in TBI. Preclinical studies suggest their potential in promoting recovery. There are fewer randomized clinical studies that evaluate efficacy. We search the kinase inhibitors approved by the FDA and traumatic brain injury as keywords on websites and analyze associated research. This review explores the therapeutic efficacy of kinase inhibitors, identifies limitations that must be addressed in future research to advance the application of FDA-approved kinase inhibitors, and emphasizes their promising potential.